Influence of High Content of Sodium Doping in Bi(pb)2212 Superconductors - Faiza, Bouaïcha; Özyüzer, Lütfi; Mosbah, Mohamed-Fayçal; Özyüzer, Lütfi (Pleiades Publishing, 2023)
Abstract: We study here, the effect of high content of sodium doping on structural and electrical properties of Bi(Pb)2212 superconductors. The X-ray analysis results showed that all the prepared samples mainly belong to the superconducting tetragonal phase Bi–(Pb)2212. SEM micrographs show that the grains are closely related and have a characteristic flat shape for the superconductor Bi (Pb) 2212. For the undoped sample, the grains are randomly distributed with an average size of 5 μm. For doped samples, the morphology changes with sodium concentration. Resistivity measurements show that all samples have a superconducting character. © 2023, Pleiades Publishing, Ltd.
Keywords: Bi–Pb–Sr–Ca–Cu–O system; Normal state; Resistivity; SHTC; Substitution; Superconductivity